Adopting a ‘move’ rather than a ‘marker’ approach to metadiscourse: A taxonomy for spoken student presentations - Ädel, Annelie (English for specific purposes (New York, N.Y.), 2023)
In metadiscourse work, what may be called a ‘marker’ approach vastly outnumbers a ‘move’ approach. This has led to a research focus on small units of analysis, typically word-based, classifying for example the pronoun I as Self-mention. This paper argues that we also need to develop a ‘move’ approach in metadiscourse studies, involving a more contextualised analysis of the discourse functions that speakers/writers use metadiscourse to perform. To support such a development, an overview is given of existing functional taxonomies for academic discourse and a specific taxonomy is presented of metadiscursive functions. The taxonomy was originally developed based on academic lectures and student essays, but is further developed as applied to spoken student presentations. The second main contribution of the article is the analysis of student presentations. The material is culled from an MA-level English-language online teaching context and compiled into a corpus of 13 presentations (20,000 words and 169 min of presentation time). The qualitative focus of the study is on the taxonomy for how metadiscourse is performed. Quantitative findings regarding the distribution of different types of metadiscourse functions are also included. Despite the widespread practice of student presentations, they have received very little research attention, but the present study maps their key discourse functions. •Much research on metadiscourse has adopted a ‘marker’ rather than a ‘move’ approach.•The unit of meaning is restricted and typically word-based in the marker approach.•The unit of meaning is extended and typically rhetorical in the move approach•It is argued that more metadiscourse research adopting a move approach is needed•A taxonomy of metadiscourse functions/moves is applied to oral student presentations